5 - Religious Factors in the Nigerian Public Sphere: Burdens and Prospects: https://doi.org/10.4314/ad.v34i3-4.63530 - Ayantayo, Jacob Kehinde (Africa Development, 2009)
The main thrust of this paper is that religious factors in the Nigerian public sphere have not received much scholarly attention. This is the gap the paper fills as it highlights religious factors in the Nigerian public sphere, which are exemplified in the spiritualisation of politics and election, the interpretation of political manifestoes, voting patterns, the choice of candidates and party leadership, oath swearing into office; the design and execution of political policy, to mention but a few. Attention is also paid to the implications of the above variables for the promotion of political ethics and ideologies. Data obtained from interviews with randomly selected political functionaries along with political historical documents were analysed and discussed within the ambit of functional theory of religion. Having examined the burdens and prospects inherent in the discourse, the paper recommends ways of making religion a continuous veritable tool for promoting good governance in Nigeria.